GENÇLİK VE SPOR İL MÜDÜRLÜĞÜ BÜNYESİNDE YAZ OKULUNDA FAALİYET GÖSTEREN SPORCULARIN SPORA KATILIM GÜDÜLERİNİN İNCELENMESİ (ELAZIĞ İL ÖRNEĞİ) - TAN, HAKAN (Fırat Üniveristesi, 2020)
Bu çalışmada Gençlik ve Spor İl Müdürlüğü Bünyesinde Yaz Okulunda Faaliyet Gösteren Sporcuların Spora Katılım Güdülerinin İncelenmesi (Elâzığ İl Örneği) amaçlanmıştır. Çalışmaya Elâzığ Gençlik ve Spor İl Müdürlüğü Bünyesinde açılan 2019 yılı yaz spor okullarında faaliyet gösteren 682 sporcu gönüllü olarak katılmıştır. Veri toplama araçları olarak tarafından hazırlanan, birinci bölümde kişisel bilgiler (yaş, cinsiyet, anne eğitim düzeyi, baba eğitim düzeyi, spor branşınız), ikinci bölümde ise; spora katılım düzeylerini belirlemek için, Gill, Gross ve Huddleston (1983) tarafından geliştirilen ve Çelebi (1993) tarafından Türkçeye uyarlaması yapılan'' Spora Katılım Güdüsü Ölçeği'' kullanılmıştır. Araştırmada SPSS 25 istatistik paket programından yararlanılmış, yüzdeler, dağılımlar, aritmetik ortalama ve standart sapmaları belirlenmiştir. İkili gruplarının karşılaştırılmasında bağımsız gruplar t testi (independentsamples t-testi), gruplar arasındaki farklılıklarda ve çoklu karşılaştırmalarda "ANOVA" testi ve Spora Katılım Güdüsü Ölçeği toplam ve alt boyutları ilişkisinin belirlenmesi gayesiyle Pearson Korelasyon Katsayısı hesaplanmıştır. Araştırmada istatistiksel analizlerin anlamlılık düzeyleri p<0,05'e göre belirlenmiştir. Araştırma bulgularına göre cinsiyet değişkenine göre sporcuların spora katılımında ''Beceri Gelişimi '' en önemli faktör olarak görülmüş ve tüm alt ölçekler açısından ise benzer bir biçimde güdülendikleri söylenebilir. Annesi ilkokul mezunu olan sporcuların Başarı, Takım Üyeliği ve Beceri için spora daha yüksek, babası ilkokul mezunu olan sporcuların Takım Üyeliğinde, üniversite mezunu olanların ise eğlence açısından spora daha çok katılım gösterdiği görülmüştür. Sporcuların branşlarına göre hareket bakımından spora katılımda fark görülmediği tüm alt boyutlardan ise etkilendiği görülmüştür. Sonuç olarak araştırmamızda ailenin eğitim düzeyi düştükçe sporcuların spora katılımı daha çok başarı, kendini kabul ettirme, ailenin eğitim düzeyi arttıkça ise spora katılımı daha çok eğlence amacıyla yaptığı sonucunu görülmüştür. Anahtar Kelimeler: Gençlik ve Spor İl Müdürlüğü, Spor Okulu, Sporcu, Güdü.

The Study Of Participation Motives To The Sports Of The Sportsmen/Sportswomen That Are Active In Summer School Within Youth And Sports Provincial Directorate (Elazığ Province Sample) In this research, it is aimed to study the participation motives of sportsmen/sportswomen to the sports (Elâzığ Province Sample) within Youth and Sports Provincial Directorate. To this research, 682 sportsmen/sportswomen that were active in 2019 summer sports schools that has been opened within Elâzığ Youth and Sports Provincial Director were participated. As data collection tools, in the first section, personal information (age, gender, education level of mother, education level of father, sport branch), and in these section, to determine the participation level to sports, "The Participation Motivation Questionnaire" that was developed by Gill, Gross and Huddleston (1983) and adapted in to Turkish by Çelebi (1993) has been used. In this research, SPSS25 statistic package program has been used; percent ages, distributions, arithmetic mean and standard deviations were determined. In comparison of binary groups, in dependent samples t-test; in differences between group sand in multiple comparisons, "Anova" test and The Participation Motivation Questionnaire; for the purpose of determining total and sub-extents, Pearson Correlation Coefficient has been calculated. In there search, the sign if icance level of statistical analyzes has been determine according to p<0,05. According to the gender variant, "Skill Development" has been seen as the most important factor in the participation of the sportsmen/ sportswomen to the sports and in terms of all subscales, it can be told that they motive in a similar way. It has been seen that the sportsmen/sportswomen that have a mother that graduated from primary school mostly participates in sports based on Performance Status, Team Membership Spirit and Skill Development; the sportsmen/ sportswomen that have a father that graduated from primary school mostly participate in sports based on Team Membership Spirit; and the sportsmen /sportswomen that graduated from universities mostly participate in sports based on entertainment sub-extents. While it has been seen that there are differences in participation motivation of sports towards team membership spirit and entertainment performance status, skill development, partner, physical relevance, spending energy and the purpose of competition according to the branches of sportsmen/ sportswomen, it has been seen that there are not any differences according to the purpose of movement, being active. Key Words: Youth and Sports Provincial Directorate, Sports School, Sportsmen /Sportswomen, Motivation
The study of participation motives to the sports of the sportsmen/sportswomen that are active in summer school within youth and sports provincial directorate (Elaziğ province sample)
Keywords: Spor